A Comparison of Cognitive-Behavioral Therapy and Pharmacotherapy vs. Pharmacotherapy Alone in Adults With Attention-Deficit/Hyperactivity Disorder (ADHD)—A Randomized Controlled Trial - Corbisiero, Salvatore; Bitto, Hannes; Newark, Patricia; Abt-Mörstedt, Beatrice; Elsässer, Marina; Buchli-Kammermann, Jacqueline; Künne, Sven; Nyberg, Elisabeth; Hofecker-Fallahpour, Maria; Stieglitz, Rolf-Dieter (Frontiers in Psychiatry, 2018)
In the treatment of adult attention-deficit/hyperactivity disorder (ADHD) the importance of psychological interventions in combination with pharmacotherapy is widely accepted in contemporary clinical routine. The natural course of the disorder seems to justify additional psychological interventions because even in patients who are highly compliant to pharmacotherapy full remission is not always achieved. The aim of the present study was to analyze the contribution of psychotherapy to the treatment of adult ADHD patients. In a randomized controlled study, the efficacy of a combined treatment of psychotherapy with pharmacotherapy is compared to pharmacological intervention alone. After initiation and stabilization of treatment with methylphenidate (MPH) in all subjects randomization to the two different treatment conditions was done. Afterwards both groups underwent treatment for about 10–12 weeks, the experimental group receiving sessions of cognitive-behavioral therapy (CBT) whereas the control group only received medication and standard clinical management (SCM). ADHD symptoms differed statistically during time but not between the two different treatment conditions. This result was the same for the single ADHD symptoms—inattention, hyperactivity, impulsivity, and emotional symptoms—and also for impairment. Individual standardized ADHD specific CBT program was not able to outperform SCM.